Studi Kearifan Lokal Petani Lembang Tumbang Datu Dalam Proses Usaha Tani Padi - Albertinhennyranteallo Albertinhennyranteallo; Awaluddin Yunus; Suardi Bakri; Helda Ibrahim (Jurnal MeA (Media Agribisnis), 2026)
Farmers in Lembang Tumbang Datu apply environmentally friendly agricultural practices, such as the use of organic fertilizers and efficient traditional irrigation systems. However, despite its significant potential, this local wisdom is often underrecognized by authorities, who tend to prioritize modern agricultural technologies that are not always suitable for local conditions. This study employs a qualitative research design aimed at understanding social phenomena from the participants’ perspectives. The sampling technique used is purposive sampling, in which informants are selected based on their relevance and in-depth knowledge of the village context being studied. In addition, snowball sampling is applied to identify additional participants through recommendations from initial key informants. The key informants in this study include traditional leaders and farmers who are familiar with the cultural practices in Lembang Tumbang Datu and are directly involved in these activities. The total number of participants in this study is 16 individuals.The results of the study show that several applications of local wisdom of the Lembang Tumbang Datu community in rice farming demonstrate a close relationship between culture, spirituality, and environmental sustainability. Each stage of farming, from Mangrara Banne, Manglammak Banne, Mantanan, to Mangrakan, is carried out with meaningful traditional rituals, reflecting gratitude, togetherness, and respect for nature and ancestors. These rituals serve to maintain harmony between humans and nature, while also regulating sustainable agricultural management. Customary prohibitions, the use of natural materials, and determining planting times based on natural signs demonstrate the high ecological value of this traditional knowledge. Thus, the agricultural system in Lembang Tumbang Datu is not only a means of food production, but also a manifestation of cultural identity that affirms food independence through spiritual, social, and ecological balance.